2020
DOI: 10.18632/aging.103989
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2, immunosenescence and inflammaging: partners in the COVID-19 crime

Abstract: Pneumonia outbreak in the city of Wuhan, China, prompted the finding of a novel strain of severe acute respiratory syndrome virus (SARS-CoV-2). Here, we discuss potential long-term consequences of SARS-CoV-2 infection, and its possibility to cause permanent damage to the immune system and the central nervous system. Advanced chronological age is one of the main risk factors for the adverse outcomes of COVID-19, presumably due to immunosenescence and chronic low-grade inflammation, both characteristic of the el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 97 publications
1
42
0
2
Order By: Relevance
“…Immunosenescence is a gradual decline in immune function that interferes with pathogen recognition, alert signaling, and clearance, causing increased susceptibility to infections and other immune-related chronic disorders, such as autoimmune diseases and cancer. 44 , 45 Inflammaging, in turn, is an increase in systemic inflammation that arises from an overactive yet ineffective alert system whereby a decline in cellular repair mechanisms causes an accumulation of genome and proteome damage, leading to systemic changes in the immune system and increased production of proinflammatory cytokines. 46 …”
Section: Methodsmentioning
confidence: 99%
“…Immunosenescence is a gradual decline in immune function that interferes with pathogen recognition, alert signaling, and clearance, causing increased susceptibility to infections and other immune-related chronic disorders, such as autoimmune diseases and cancer. 44 , 45 Inflammaging, in turn, is an increase in systemic inflammation that arises from an overactive yet ineffective alert system whereby a decline in cellular repair mechanisms causes an accumulation of genome and proteome damage, leading to systemic changes in the immune system and increased production of proinflammatory cytokines. 46 …”
Section: Methodsmentioning
confidence: 99%
“…Indeed, our investigations have shown that in mice with thymic involution, there was increased lymphocyte infiltration into self-tissues, including the lung [ 67 ]. Although there is increasing interest in the correlation between immunosenescence and the increased risk of COVID-19 mortality in the elderly, more research is needed to fully elucidate the role of pre-existing lung inflammation and infiltration of potentially self-reactive T cells during COVID-19 pathogenesis [ 73 , 74 , 75 , 76 ].…”
Section: How Does Age-related Thymic Involution and Subsequent T-cmentioning
confidence: 99%
“…Liver biopsy of the deceased patients showed mild lobular and portal vein activity and moderate microvascular steatosis [ 11 ]. Previous studies have demonstrated that a cytokine storm is triggered when the immune system overreacts to infection [ 34 , 35 ]. And cytokine storm is considered to be an important factor leading to acute respiratory distress syndrome and multiple organ dysfunction syndrome [ 36 ].…”
Section: Discussionmentioning
confidence: 99%